Association between Morphodynamic Variables by Transesophageal Echocardiography and CHA2DS2-Vasc Values - Linhares,Renata Rejane (2019)
Abstract Background: In atrial fibrillation (AF), the CHA2DS2-VASc score calculates the risk for stroke. Di Biase classified the left atrial appendage (LAA), using magnetic resonance imaging, into 4 morphological types and correlated it with cerebrovascular events. Transesophageal echocardiography (TEE) also evaluates LAA and is a more widespread technique. Objective: To evaluate, using TEE, the possibility of characterizing LAA and to analyze its morphological aspects using the CHA2DS2VASc score. Methodology: A total of 247 patients were divided into three groups considering the CHA2DS2-VASc score: Group 1: 0 and 1; Group 2: 2 and 3 and, Group 3: ≥ 4 points. TEE produced the echocardiographic data. LAA was classified into thrombogenic and non-thrombogenic morphologies. In the analysis of statistical tests, a significance level of 5% was adopted. Results: The average age was 50 and 16.2% presented AF. In Group 1, we observed normal variables with a lower prevalence of AF (8.7%, p < 0.001). In group 2, spontaneous contrast was detected in 26.7%, (p < 0.001), thrombus in 6.7% (p = 0.079) and flow velocity in LAA < 0.4 m/s in 22.7% (p < 0.001) of the cases. Group 3 presented the highest percentages of AF (31.8%, p < 0.001), stroke/TIA (77.3%, p < 0.001), EF < 55% (18.2%, p = 0.010) and higher prevalence of thrombogenic type LAA (72.7%, p = 0.014). A higher occurrence of stroke/TIA was observed in patients with thrombogenic LAA (25.2%) compared to the non-thrombogenic group (11.2%), (p = 0.005). Conclusions: The thrombogenic morphology of LAA identified in TEE presented a higher risk of stroke regardless of the CHA2DS2VASc score. Patients with higher scores had greater abnormalities in echocardiographic variables.